DEVELOPING E-LAS FOLKLORE: ENHANCING READING LITERACY THROUGH ‘RATU AGUNG’ TO SUPPORT STUDENTS READING LITERACY SKILLS - Alwi, Zahra; Putri, Eka; Ilma Indra Putri, Ratu; Aulia Oktarina, Detia; Zulkardi (English Review: Journal of English Education, 2025)
This research aims to develop web-based student activity sheets (e-LAS) designed to enhance literacy skills by adapting the Ratu Agung folklor into short stories. The development process employed the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through interview, observation, and evaluation stages, and analyzed using both qualitative and quantitative approaches. The study involved 10th-grade students at Athalla Putra Health Vocation School in Palembang. The expert evaluation of final e-LAS product yielded scores of 79,54 (good) for content relevance, 92,50 (very good) for presentation, and 91,66 (very good) for language, with an overall average of 87,90. Initial trials revealed that students were unfamiliar with analyzing and extracting information for complete text. Nonetheless, 84,61% of students achived the set learning objectives, indicating a high level of product effectiveness. These results suggest that the developed e-LAS can serve as a valuable aternative instruction tool to support literacy development and foster students’ creativity through culturally rooted literary expressions.